Performance Study on a Single-Screw Expander for a Small-Scale Pressure Recovery System - Guoqiang Li (Energies, 2016)
A single-screw expander with 195 mm diameter is developed to recover pressure energy in letdown stations. An experiment system is established using compressed air as a working fluid instead of natural gas. Experiments are conducted via measurements for important parameters, such as inlet and outlet temperature and pressure, volume flow rate and power output. The influence of inlet pressure and rotational speed on the performance are also analyzed. Results indicate that the single-screw expander achieved good output characteristics, in which 2800 rpm is considered the best working speed. The maximum volumetric efficiency, isentropic efficiency, overall efficiency, and the lowest air-consumption are 51.1 kW, 83.5%, 66.4%, 62.2%, and 44.1 kg/(kW·h), respectively. If a single-screw expander is adopted in a pressure energy recovery system applied in a certain domestic natural gas letdown station, the isentropic efficiency of the single-screw expander and overall efficiency of the system are found to be 66.4% and 62.2%, respectively. Then the system performances are predicted, in which the lowest methane consumption is 27.3 kg/(kW·h). The installed capacity is estimated as 204.7 kW, and the annual power generation is 43.3 MWh. In the next stage, a pressure energy recovery demonstration project that recycles natural gas will be established within China, with the single-screw expander serving as the power machine.